Beta (+)-Thalassaemia in the Po river delta region (northern Italy): genotype and beta globin synthesis. Issue 1 (February 1985) - Del Senno, L; Pirastu, M; Barbieri, R; Bernardi, F; Buzzoni, D; Marchetti, G; Perrotta, C; Vullo, C; Kan, Y W; Conconi, F
Abstract : Six beta(+)-thalassaemic patients from the Po river delta region have been studied. Using synthetic oligonucleotides as specific hybridisation probes, the beta(+) IVS I mutation (G—-A at position 108) was demonstrated. This lesion and the enzyme polymorphism pattern in the subjects examined are the same as have been described for other Mediterranean beta(+)-thalassaemias. Antenatal diagnosis through DNA analysis of beta(+)-thalassaemia is therefore possible. The production of beta globin in a beta(+), homozygote and in a beta (+), beta(0) 39 (nonsense mutation at codon 39) double heterozygote is approximately 20% and 10% respectively of total non-alpha globin synthesis. Despite some overlapping of the results, similar beta globin synthesis levels have been obtained in 43 beta(+)-thalassaemia patients. This suggests that in the Po river delta region the most common thalassaemic genes are beta(0) 39 and beta(+) IVS I.